In vitro evaluation of bond strength of sealers after using various irrigants and Erbium-Yttrium-Aluminum-Garnet laser irradiation on radicular dentin surface: A SEM study - Navdeep Kaur; Shikha Bhandari; Pardeep Mahajan; Prashant Monga; Sonam Mahajan; Nitika Bajaj (Wolters Kluwer Medknow Publications, 2019)
Aim: The aim of this in vitro study was to evaluate and compare the push-out bond strength of Adseal and mineral trioxide aggregate (MTA) Fillapex sealer after using various irrigants and Erbium-Yttrium-Aluminum-Garnet (Er:YAG) laser irradiation on radicular dentin surface. Materials and Methods: A total of 80 freshly extracted human permanent maxillary anterior teeth were sectioned transversally below the cemento-enamel junction. The remaining root portion was sectioned to get 4-mm thick dentin disc from coronal end of the root, with straight handpiece, and diamond disc. Root canal of specimens was prepared with bur to create space for sealer placement. Specimens were divided into eight groups of 10 samples each, as per irrigants and sealer used. In Group 1, 3, 5, and 7 specimens irrigated with distilled water, NaOCl, Ethylenediaminetetraacetic acid (EDTA), and Er:YAG laser, respectively, and obturated with Adseal sealer. In Group 2, 4, 6, and 8 irrigated with distilled water, NaOCl, EDTA, and Er:YAG laser, respectively, and obturated with MTA Fillapex sealer. After sealer setting, the force used to remove the sealer was evaluated using universal testing machine. Recorded force used to calculate the push-out bond strength in Megapascals and scanning electron microscopy examination was done for specimens. Results: Adseal sealer had significantly higher bond strength than MTA Fillapex sealer, irrespective of irrigant used. The highest bond strength was seen in specimens irrigated with EDTA and obturated with Adseal sealer and least in specimens irrigated with distilled water and obturated with MTA Fillapex sealer. Conclusion: Adseal sealer had significantly higher bond strength than the MTA Fillapex sealer. EDTA irrigation showed better smear layer removal, followed by Er:YAG laser irradiation, then NaOCl, least by distilled water.